Pembaharuan Hukum Acara Pidana Berwawasan Hak Asasi Manusia dalam Perspektif Teori Konstrusionisme - Muhammad Arif Setiawan (Fakultas Hukum Universitas Islam Indonesia, 2002)
In theoretic perspective for constructionism, each of the parties involved in the process on criminai court is suitable with the position andthe roie of each the process for criminal court it self would make ideas to decide for their own objectives andto act as according to the objectives assigned deliberateiy. In doing this action, then they give the meaning to their action or behaviour and as well as they will give thereasons about theaction to carryout. The consequence isthe raising on different meaning. These writings describe about the innovation oflaw on criminal procedure in the frame of Human Right in the theoretical perspective of constructionism.